Penyusunan Roadmap Strategis Tata Kelola TI LMS Sinau Berdasarkan Maturity Level COBIT 2019 - Irma Santikarama; Faiza Renaldi; Dea Destiani (Jurnal Informatika Terpadu, 2026)
This study aims to assess the maturity level of information technology (IT) governance and to develop a strategic improvement roadmap for the internally developed SINAU Learning Management System at Universitas Jenderal Achmad Yani using the COBIT 2019 framework. A mixed-method approach with a convergent design was employed, combining quantitative data from questionnaire-based maturity assessments with qualitative insights from in-depth interviews. The results indicate that the overall IT governance maturity is at Level 2 (Managed), where processes are operational but not yet fully documented or standardized across organizational units. The largest governance gaps were identified in service agreement management, change and release management, and performance monitoring and evaluation. Based on the gap analysis and qualitative findings, a phased strategic roadmap was formulated to guide governance improvements toward Level 3 (Established Process). The study concludes that strengthening formal policies, process documentation, and monitoring mechanisms is essential to ensure sustainable LMS governance and alignment with institutional objectives in higher education.